The Impact of Strategic Leadership to Achieving Strategic Success : “An analytical study of the opinions of managers in a sample of small and medium projects in Erbil Governorate” - MOHAMMED, ARDALAN Y.; WALI , DR. AHLAM I.; RASHID , DR. WIRYA N. (Polytechnic Journal of Humanities and Social Sciences, 2024)
Abstract: The aim of this research is to determine the impacts of strategic leadership through dimensions (the alignment of people, systems, and resources in an organization or project). In enhancing strategic success in the projects in Erbil Governorate in the Iraqi Kurdistan Region. Descriptive analytical methods have been used to analyze the data to describe the variables and dimensions in the study. Then the relationship between an independent variable (strategic leadership) and the dependent variable (strategic success) has been analyzed. The research was conducted on small and medium projects in Erbil Governorate. Questionnaire forms have been used as data collection tools. The sample size frame of the study is (205) Managers who answered the questions. SPSS v23 used to analyze data. As a result of the data analysis, several results were obtained by describing and identifying both variables in the study, the most important of which is the existence of a direct and significant relationship between the dimensions of strategic leadership and the dimensions of strategic success. The dimension of the strategic leadership variable also has had a positive impact on the strategic success. Finally, a number of recommendations for future research are proposed, the most important of which is that attention should be paid to the implementation of the study variables in all sectors in Iraqi Kurdistan The study seeks to reach theoretical and practical conclusions in the light of which appropriate recommendations are proposed. Keyword: Strategic leadership, Strategic success, Projects in Erbil Governorate.